MASSIVE PULMONARY FIBROSIS AFTER SEVERE BILATERAL PNEUMONIA AS POST COVID-19 COMPLICATION - Ivanovska, Beti Zafirova; Stojkovikj, Jagoda (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
A large number of hospitalized COVID-19 survivors show that persistent symptoms, radiographic abnormalities and physiological impairments exist months after the initial illness. Persistent chest imaging abnormalities and histopathological findings of lung fibrosis were also found in a majority of survivors of the SARS-CoV-1 suggesting that the SARS viruses may lead to a worse fibroproliferative response than other pneumonia. Our patient had a severe COVID-19 pneumonia, followed by massive infiltrative changes in both lungs in addition to massive pulmonary fibrosis. After the initial treatment in one of the COVID-19 centers in the Clinical Center in Skopje, the patient with post-COVID-19 (more precisely pulmonary fibrous changes of the lungs) was referred for further treatment to the University Clinic for Pulmonology in a severe clinical condition, where he was treated at an outpatient basis in the period of several months. During that time the condition improved, with a significant withdrawal of the X-ray finding of the lungs, which was registered on CT from 5.5.2021. He is still under observation. The robust responses of corticosteroid therapy in our case presenting a radiological pattern of organizing pneumonia allowed the patient to return to his baseline clinical condition. But due to the persistence of X-ray residual changes he is under our regular observation. Keywords : COVID-19, bilateral pneumonia, massive pulmonary fibrosis. https://doi.org/10.55302/JMS2143144zi